A CIDR-based AI protocol establishes pregnancy in repeat-breeder dairy cattle - HONPARKHE, M; GHUMAN, S P S; SINGH, JAGIR; DHALIWAL, G S (The Indian Journal of Animal Sciences, 2011)
The objectives of this study were to document ovarian and endocrine responses as well as pregnancy establishment following the treatment of repeat-breeder crossbred dairy cattle with a progesterone-releasing controlled internal drug release (CIDR) -based artificial insemination (AI) protocol. Cattle (25) received prostaglandin F2a (PGF2a , 500Î¼g) on day 0, concurrent with the intravaginal placement of CIDR (1.38 g progesterone) for 15 days, followed by gonadotropin releasing hormone (GnRH) analogue (20Î¼g) administration at the spontaneous onset of estrus (day 17, 18 or 19). About 10 h after GnRH, AI was carried out in all the cattle. On day 0, a corpus luteum (CL, 13.7Â±1.4 mm) and a large follicle (11.1Â±0.6 mm) were detectable in all the cattle. On day 15, the former was regressed (P